2019
DOI: 10.3390/ma12081255
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Nanocrystalline Al-Zn-Mg-Cu Alloy Prepared by Mechanical Alloying and Spark Plasma Sintering

Abstract: In this study, Al, Zn, Mg and Cu elemental metal powders were chosen as the raw powders. The nanocrystalline Al-7Zn-2.5Mg-2.5Cu bulk alloy was prepared by mechanical alloying and spark plasma sintering. The effect of milling time on the morphology and crystal structure was investigated, as well as the microstructure and mechanical properties of the sintered samples. The results show that Zn, Mg and Cu alloy elements gradually dissolved in α-Al with the extension of ball milling time. The morphology of the ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Additionally, with the existence of QC peaks, the intensity of the elemental peaks diminished, specifically at the angles of 2θ = 41.88 and 47.45°. Using the well-known Williamson-Hall’s equation [10,11], the crystallite/quasicrystal size of the coated powders after 360 min of BM was calculated to be 17.7 nm, while the corresponding crystallite size was 55.5 nm for the raw powder system. This variation can be originated from the formation of a much harder QC phase in the coated powder system with increasing the milling time, which causes acceleration of reduction in crystallite/quasicrystal size.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, with the existence of QC peaks, the intensity of the elemental peaks diminished, specifically at the angles of 2θ = 41.88 and 47.45°. Using the well-known Williamson-Hall’s equation [10,11], the crystallite/quasicrystal size of the coated powders after 360 min of BM was calculated to be 17.7 nm, while the corresponding crystallite size was 55.5 nm for the raw powder system. This variation can be originated from the formation of a much harder QC phase in the coated powder system with increasing the milling time, which causes acceleration of reduction in crystallite/quasicrystal size.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Recent studies on 7xxx PM alloys have shown that HEBM results in the dissolution of precipitates present in powders and a more homogeneous distribution of solutes. 16,17 The oxide and nitride surface layers of the powder can be introduced into the matrix during milling, which plays an important role in maintaining the fine grain structure and dispersion strengthening in sintered and heat-treated alloys. 18 Al alloy powders have also been used in additive manufacturing (AM) processes for applications in the aerospace, defence, and automotive industries.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical alloying as a method of solid-state particle processing that involves m Among various metal matrix composites (MMCs), the 7xxx series, which consists of minor alloying elements such as Zn, Mg, and Cu, have garnered more attention compared to conventional metal-based alloys for use as matrix materials. This is due to their high specific mechanical properties, lightweight nature, and easy availability [49,50]. Moreover, copper holds significant importance in the manufacturing industry as it is extensively utilized for the production of a wide variety of products.…”
Section: Introductionmentioning
confidence: 99%